Being a turker - Hanrahan, Benjamin V.; O'Neill, Jacki; Gupta, Neha; Martin; David (Proceedings of the 17th ACM conference on Computer supported cooperative work & social computing, pp. 224-235., 2014)
We conducted an ethnomethdological analysis of publicly available content on Turker Nation, a general forum for Amazon Mechanical Turk (AMT) users. Using forum data we provide novel depth and detail on how the Turker Nation members operate as economic actors, working out which Requesters and jobs are worthwhile to them. We show some of the key ways Turker Nation functions as a community and also look further into Turker-Requester relationships from the Turker perspective – considering practical, emotional and moral aspects. Finally, following Star and Strauss [25] we analyse Turking as a form of invisible work. We do this to illustrate practical and ethical issues relating to working with Turkers and AMT, and to promote design directions to support Turkers and their relationships with Requesters.